A comparative study of the reading comprehension of english second language learners between urban and rural schools in Limpopo Province - Mboacha, Evelyne (My University, 2015)
This study explores reading comprehension in rural and urban schools. The study was conducted against the background that it takes five to seven years for second language (L2) learners to become proficient in the English language. Generally, learners in rural schools use the mother tongue as the language of schooling. English is introduced only as a medium of instruction at Grade Four, although this is not often implemented or applied. By contrast, in urban schools the medium of instruction is English from as early as Grade R. As a result of this discrepancy in practice, learners in urban and rural schools have different experiences. This study was conducted to gain more insight into the reading comprehension and reading preferences of learners in both rural and urban schools, especially since there is a mismatch between the language policy on paper and the language realities on the ground. Descriptive statistics and analysis of variance was used to measure differences, determine mean scores and analyse tendencies of preferences. The total mean score for reading comprehension obtained by learners from Grade Four Rural (GFR) was 1.48, whereas the mean score for Grade Four Urban (GFU) was 1.92. From these scores, it is evident that the learners from GFR gave comparatively more wrong answers than their counterparts from GFU. Similarly, the results from the Grade Seven learners showed that there was a significant difference in mean scores (or performance) between Grade Seven Rural (GSR) and Grade Seven Urban (GSU) since the mean score for GSR was 1.37, while that for GSU was 2.24. The English language was preferred by the majority of the learners. The results of the study show that learners lack adequate proficiency in English second language to enable them to use it solely and effectively as a medium of instruction and learning. In addition, a low reading comprehension performance was noted, with the majority of the participants scoring below 50%. Recommendations are provided to improve the reading comprehension and performance of the learners.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2015.
Keywords: Reading comprehension; English second language; Reading (Primary) -- South Africa -- Limpopo; Comprehension -- Testing; Language and languages -- Study and teaching